Leaf anatomical characteristics of Avicennia L. and some selected taxa in Acanthaceae - Mohd Yunus, Noor Syaheera; Talip, Noraini; A. K., Radhiah; Che Amri, Che Nurul Aini (Malaysian Nature Society, 2015)
The proposed placement of Avicennia L. into Acanthaceae had been made based only on molecular data. The main objective of this study is to investigate whether anatomical leaf characteristics of the Avicennia species support this placement. This study also aims to determine the leaf anatomical characteristics and their taxonomic value for some selected taxa ofAcanthaceae. Seven species were studied, namely A. alba Blume, A. officinalis L., A. lanata Ridley, Justicia gendarussa Burm. f., J. betonica L., Strobilanthes crispa Blume and Asystasia gangetica subsp. micrantha (L.) T. Anderson. Methods used were sectioning using sliding microtome, leaf clearing, epidermal peels, and observation under a light microscope. Findings have shown great differences between Avicenniaspecies andother studied taxa. There are eleven outstanding leaf anatomical variations which may be used to distinguish all Avicennia species from the others, such as the presence and absence of brachysclereids, hypodermal layers, cystoliths and the presence of denture on the abaxial side of leaf margin, type of trichomes and stomata, areolar venation, marginal outline, shape of vascular bundles in the midrib, and the pattern of anticlinal walls on the adaxial and abaxial epidermis cells. The presence of mucilaginous idioblasts cells is common in all species studied. This study has shown that the genus Avicennia does not share similar leaf anatomical characteristics with the other taxa in Acanthaceae. As a conclusion, the placement of the genus Avicennia into the Acanthaceae has not been supported by leaf anatomical characteristics; therefore, it is suggested that this placement be revised.